Proposta de um framework para análise dos impactos da Indústria 4.0 na cadeia de valor - Klingenberg, Cristina Orsolin (Universidade do Vale do Rio dos Sinos, 2020)
Industry 4.0 (I4.0) will impact the value chains in such a way that it will be necessary to rethink business and the competitive landscape. To define strategies related to the phenomenon, organizations must look more broadly at it, trying to understand its impact on value creation. Using the Design Science Research (DSR) method, this research proposes a framework for companies and governments to discuss and learn about the impacts of I4.0 on value chains. The artifact consists of five blocks of analysis. The first two blocks, changing environment and new value proposition, are contextual, so that the aspects that are driving the transformation are understood. The third block – Industry 4.0 – is dedicated to the discussion of I4.0 concepts and technologies applied to the chain being analyzed. The fourth block, the value chain, is the center of the analysis, as it aims to understand the expected impacts on the different elements of the value creation process: activities, flows, actors and governance. In the last block – value capture – the effects of the transformation of the chain on appropriability by the participants in the value creation process are discussed. The practical contribution of this thesis is the proposition of the artifact to guide professionals in the discussion and learning about the impacts of I4.0 on the value chains. Academically, the work presents advances in the field of value chain studies for considering four dimensions of the construct and for proposing it to analyze transformation instead of performance. In addition, it contributes to the DSR research method, with the suggestion of a method of analyzing interviews with specialists.
Keywords: Cadeia de valor; Indústria 4.0; Transformação digital; Value Chain; Industry 4.0; Digital transformation; ACCNPQ::Engenharias::Engenharia de Produção